2012
DOI: 10.1364/oe.20.023978
|View full text |Cite
|
Sign up to set email alerts
|

Random lasing in blue phase liquid crystals

Abstract: Random lasing actions have been observed in optically isotropic pure blue-phase and polymer-stabilized blue-phase liquid crystals containing laser dyes. Scattering, interferences and recurrent multiple scatterings arising from disordered platelet texture as well as index mismatch between polymer and mesogen in these materials provide the optical feedbacks for lasing action. In polymer stabilized blue-phase liquid crystals, coherent random lasing could occur in the ordered blue phase with an extended temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 26 publications
0
46
0
Order By: Relevance
“…This observation has encouraged the development of 3D tunable laser sources for integrated photonic circuit applications [104,111]. Recently, Chen et al observed the potential for dye doped cubic BPs to give off coherent random laser [112]. Much different from the bandedge lasing, interferences and recurrent multiple scattering arising from the grain boundaries in a BP polycrystal provides the optical feedbacks for such laser action.…”
Section: Control Of Bp Photonic Bandgapmentioning
confidence: 99%
“…This observation has encouraged the development of 3D tunable laser sources for integrated photonic circuit applications [104,111]. Recently, Chen et al observed the potential for dye doped cubic BPs to give off coherent random laser [112]. Much different from the bandedge lasing, interferences and recurrent multiple scattering arising from the grain boundaries in a BP polycrystal provides the optical feedbacks for such laser action.…”
Section: Control Of Bp Photonic Bandgapmentioning
confidence: 99%
“…Recent studies have shown that another mesophase, namely, Blue-Phase Liquid Crystals (BPLC) present promising alternatives to NLC for electro-and nonlinear optics [32][33][34][35][36][37][38][39][40][41][42][43][44]. In this unique class of optical materials formed by mixing a chiral compound and nematics, the molecules self-assemble (without cell-surface alignment) into tightly wound defect-spirals that form 3-D body-centered cubic or simple cubic lattices with sub-wavelength lattice constants, cf.…”
Section: Intense Laser Induced Lattice Distortion In Bplc With Nanosementioning
confidence: 99%
“…There have also been recent studies of another phase of chiral nematic liquid crystals, namely, Blue-Phase Liquid Crystals (BPLC) and their polymer-stabilized forms (PSBPLC) that presented promising polarization-and alignment-free alternatives [5,[92][93][94][95][96][97][98][99] for nonlinear optics as well as electro-optics. In this unique class of optical materials formed by mixing chiral and achiral nematics (with or without polymer stabilization), the molecules self-assemble into tightly wound defect-spirals that form 3-D cubic or BCC lattices with sub-wavelength lattice constants.…”
Section: Multiple Time Scales Nonlinearities Of Nematic Liquid Crystamentioning
confidence: 99%